Les signes de l’interaction esprit-humain - Fanny Tilmant (Ateliers d'Anthropologie)
On the Zanzibar Archipelago, the terms masheitani (sing. sheitani) and majini (sing. jini) designate invisible beings that share the world with human beings. Stories about these “spirits” are numerous, and describe particularly beings capable of slipping into the dreams of individuals, momentarily borrowing their body, or unexpectedly appearing in the course of everyday life. These stories nevertheless indicate a certain polysemy in the inhabitants’ perceptions, actions and interpretations connected with the relations that can be developed with masheitani. Through the islanders’ accounts of their experiences, this article highlights the characteristics of the interactions between human beings and invisible beings in everyday life. It describes how these relations hinge on learning sensations, symptoms and signs that are linked with the manifestation of masheitani and enable them to be identified.